Long-term occupational exposure to the insecticides aldrin dieldrin, endrin, and telodrin - Versteeg, J. P. J. (1973)
Versteeg, J. P. J. and Jager, K. W. (1973).British Journal of Industrial Medicine,30, 201-202. Long-term occupational exposure to the insecticides aldrin, dieldrin, endrin, and telodrin. A medical survey of 233 long-term insecticide workers has previously been published. Fifty-two of them had left employment at the time of the original publication. All members of this group could be traced. No unexpected adverse effects on health were found. Their disease pattern and general well-being were not different from those in the original group.